Perceiving Political Polarization in the United States: Party Identity Strength and Attitude Extremity Exacerbate the Perceived Partisan Divide. (March 2015) - Westfall, Jacob; Van Boven, Leaf; Chambers, John R.; Judd, Charles M.
An important component of political polarization in the United States is the degree to which ordinary people perceive political polarization. We used over 30 years of national survey data from the American National Election Study to examine how the public perceives political polarization between the Democratic and Republican parties and between Democratic and Republican presidential candidates. People in the United States consistently overestimate polarization between the attitudes of Democrats and Republicans. People who perceive the greatest political polarization are most likely to report having been politically active, including voting, trying to sway others' political beliefs, and making campaign contributions. We present a 3-factor framework to understand ordinary people's perceptions of political polarization. We suggest that people perceive greater political polarization when they (a) estimate the attitudes of those categorized as being in the "opposing group"; (b) identify strongly as either Democrat or Republican; and (c) hold relatively extreme partisan attitudes—particularly when those partisan attitudes align with their own partisan political identity. These patterns of polarization perception occur among both Democrats and Republicans.